Preliminary Considerations for the Development of Ecological Tourism in the Amazonian Communities of Ecuador - Álvarez Cortez, Luis Eduardo (2016)
In this review and disclosure article, we first present theoretical considerations and legal premises for the development of ecological tourism in indigenous communities in the Ecuadorian Amazon of Pastaza, the result of a thorough bibliographical and documentary research on the subject. Ecotourism is a trend different from traditional tourism and contrasts with the "maximum profitability" approach. Ecotourism, nature and culture are uniquely interrelated in the Amazon, unique and important for its anthropological aspects and biodiversity. This community activity with features of cooperativism privileges the sustainability, appreciation-preservation and improvement of the natural and cultural environment that welcomes travelers. It represents a viable alternative of sustainable development that satisfies the needs of tourists and residents of the destination without compromising future generations that inhabit it-visit. However, native communities lack the appropriate tools and scientific-technical strategies, as well as the business skills and competences to achieve local tourism ventures effectively that comply with the Ecuadorian Government's Strategic Tourism Plan for tourism sustainability. The current method of development based on the "community push", needs to be changed by a well-founded and comprehensive tourism organization and management approach that guarantees eco-tourism entrepreneurship with appropriately prepared and trained native nationalities